The Effect of Using Problem Based Learning Models on Students' Learning Outcomes in Science Subjects - Sri Utami; Ahmad Susanto; Fitri Arniati (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2025)
This study aims to analyze the impact of the implementation of the Problem Based Learning (PBL) learning model on improving student learning outcomes in science subjects for grade VIII, especially Newton's Law material, and to identify the challenges faced in its implementation. The study used a quantitative approach with a pretest-posttest design, which compared student learning outcomes before and after the implementation of PBL. Data were collected through objective tests. The results showed an increase in the average student score from 69 (less category) to 74.6 (good category) after the implementation of PBL. Data analysis using paired sample correlation tests showed a significant relationship between conventional learning methods and PBL, with a significance value of 0.000